Analysis of Temperature-dependent Extended X-ray Absorption Fine Structure Oscillation of Distorted Crystalline Cadmium - Sy Tien, Tong (Communications in Physics, 2022)
In this paper, the temperature-dependent extended X-ray absorption fine structure (EXAFS) of distorted crystalline cadmium has been analyzed using an efficient calculation-model. The analysis procedure is based on evaluating the influence of temperature on the phase shift and amplitude reduction of EXAFS oscillation that is expressed in terms of the EXAFS Debye-Waller factor. The anharmonic EXAFS cumulants are calculated by expanding the anharmonic correlated Debye model based on the anharmonic effective potential that depends on the structural characteristics of distorted crystalline cadmium. The numerical results satisfy well with those obtained using the experimental data and other models at various temperatures. The obtained results indicate that this theoretical model is useful for calculating and analyzing the experimental EXAFS data of distorted crystalline metals.